Magnetic Dynamic Polymers for Modular Assembling and Reconfigurable Morphing Architectures. Issue 30 (19th June 2021) - Kuang, Xiao; Wu, Shuai; Ze, Qiji; Yue, Liang; Jin, Yi; Montgomery, S. Macrae; Yang, Fengyuan; Qi, H. Jerry; Zhao, Ruike
Abstract: Shape‐morphing magnetic soft materials, composed of magnetic particles in a soft polymer matrix, can transform shape reversibly, remotely, and rapidly, finding diverse applications in actuators, soft robotics, and biomedical devices. To achieve on‐demand and sophisticated shape morphing, the manufacture of structures with complex geometry and magnetization distribution is highly desired. Here, a magnetic dynamic polymer (MDP) composite composed of hard‐magnetic microparticles in a dynamic polymer network with thermally responsive reversible linkages, which permits functionalities including targeted welding for magnetic‐assisted assembly, magnetization reprogramming, and permanent structural reconfiguration, is reported. These functions not only provide highly desirable structural and material programmability and reprogrammability but also enable the manufacturing of functional soft architected materials such as 3D kirigami with complex magnetization distribution. The welding of magnetic‐assisted modular assembly can be further combined with magnetization reprogramming and permanent reshaping capabilities for programmable and reconfigurable architectures and morphing structures. The reported MDP are anticipated to provide a new paradigm for the design and manufacture of future multifunctional assemblies and reconfigurable morphing architectures and devices. Abstract : Magnetic dynamic polymer composites composed of hard‐magnetic microparticles in thermally reversible dynamic polymer networks for multifunctional assemblies and reconfigurable architectures are reported. These composites integrate the functionalities of targeted welding of modular assembling with complex actuation, magnetization reprogramming with altered shape‐morphing mode, and remote‐controlled permanent structural reconfiguration, opening a new avenue for manufacturing multifunctional and reconfigurable morphing architectures and devices.